DATA PROCESSING USING THE IBM SPSS MODELER TOOL - Čižiks, Jānis; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2019)
IBM SPPS Modeler platform is the commercial rival of RapidMiner platform, characterized by a low entrance threshold for beginners. Nonsense for beginners is expressed by the "autopilot" modes. Auto models (Auto Numeric, Auto Classifier) distinguishes several possible patterns with different parameters, which identify them better. Not an experienced analyst, using such a solution, is able to develop an adequate model. The SPSS user interface is constantly improving, making the system intuitive to understand. For simple tasks, such as fuling, there is no need for preparation in principle. This makes IBM SPSS Modeler a good solution for data analysis for beginners.